Model of the risk assessment of hand-arm system vibrations in cycling: Case of cobblestone road - Munera, M.; Chiementin, X.; Murer, S.; Bertucci, W. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
Vibrations experienced by the human body are a well-known and widely studied risk factor in the industrial world. These are transmitted to the whole body or parts of it (like the hand-arm system) and are measured and limited according to international standards and European directives. However, despite the ubiquity of vibrations, their effects are little studied in sport. Vibrations can induce discomfort, thus degrading performance, or even cause musculoskeletal disorders. This article presents a numerical methodology to estimate the vibration total value transmitted to the hand-arm system during the practice of cycling over cobblestone roads. This assessment is achieved using a modeling of the excitation source representing the displacement over the cobblestone, as well as the vibratory behavior of the cycle. The influence of the model parameters will be discussed. Finally, the estimated vibration total value will be compared to values obtained from field test conditions.